2021
DOI: 10.1002/ptr.7107
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin as potential tool against SARS‐Cov‐2: In silico spike receptor‐binding domain and main protease molecular docking analysis, and in vitro endothelial protective effects

Abstract: The spread of SARS‐CoV‐2, along with the lack of targeted medicaments, encouraged research of existing drugs for repurposing. The rapid response to SARS‐CoV‐2 infection comprises a complex interaction of cytokine storm, endothelial dysfunction, inflammation, and pathologic coagulation. Thus, active molecules targeting multiple steps in SARS‐CoV‐2 lifecycle are highly wanted. Herein we explored the in silico capability of silibinin from Silybum marianum to interact with the SARS‐CoV‐2 main target proteins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Quercetin’s bioavailability is comparatively better but remains constrained by intestinal efflux and biliary excretion [ 64 ]. More promisingly, EGCG, hispidulin, icariin, quercetin, and rutin can cross the BBB; silibinin cannot, while the permeability of chrysin and formononetin remains unclear [ 17 , 65 , 66 , 67 , 68 ]. In this light, developing novel formulations to enhance the bioavailability and brain delivery of flavonoids is of key interest in advancing synergistic anti-GBM therapy.…”
Section: Key Considerations and Challengesmentioning
confidence: 99%
“…Quercetin’s bioavailability is comparatively better but remains constrained by intestinal efflux and biliary excretion [ 64 ]. More promisingly, EGCG, hispidulin, icariin, quercetin, and rutin can cross the BBB; silibinin cannot, while the permeability of chrysin and formononetin remains unclear [ 17 , 65 , 66 , 67 , 68 ]. In this light, developing novel formulations to enhance the bioavailability and brain delivery of flavonoids is of key interest in advancing synergistic anti-GBM therapy.…”
Section: Key Considerations and Challengesmentioning
confidence: 99%
“… In terms of distribution indicators, the size of the distribution (VDss) is considered high if its value is greater than 0.45 [ 75 ]. The standard value for blood-brain barrier (BBB) permeability is good if its value is more than 0.3 and poor if LogBB < -1 [ 76 ]. For the CNS index, compounds with LogPS > -2 are considered capable of penetrating the CNS, whereas compounds with LogPS < -3 are considered incapable of penetrating the CNS [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present virtual issue contains review addressing the potential of flavonoids, curcumin, resveratrol and silibinin in attenuating lung injury and cytokine storm associated with the disease (Derosa et al, 2021 ; Di Petrillo, Orrù, Fais, & Fantini, 2021 ; El‐Missiry, Fekri, Kesar, & Othman, 2021 ; Gour, Manhas, Bag, Gorain, & Nandi, 2021 ; Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021 ; Palit, Mukhopadhyay, & Chattopadhyay, 2021 ; Pawar & Pal, 2020 ; Santana et al, 2021 ). Studies on specific polyphenols showed that (a) kaempferol inhibited the SARS‐CoV‐2 main protease (3CLpro) (Khan et al, 2021 ), (b) oroxylin suppressed the entrance of the SARS‐CoV‐2‐spiked pseudotyped virus into ACE2 cells (Gao et al, 2021 ), (c) resveratrol inhibited the replication of SARS‐CoV‐2 in cultured Vero cells (M. Yang et al, 2021 ) and (d) silibinin interacted with SARS‐CoV‐2 main target proteins (e.g., spike protein RBD and Mpro residues) (Speciale et al, 2021 ). Clinical investigations showed the efficacy of nano‐curcumin formulations in the management of mild to moderate hospitalized patients, being curcumin able to accelerate the recovery of the acute inflammatory phase (Hassaniazad et al, 2021 ; Saber‐Moghaddam et al, 2021 ).…”
Section: Polyphenolsmentioning
confidence: 99%